Silicone Intubation Versus No Intubation In Dacryocystorhinostomy For Nasolacrimal Duct Obstruction: A Systematic Review - Ida Ayu Bintang Maui Putri; Anak Agung Avrella Shora Yuananda; Ni Made Ayu Trisnadewi Suyasa (International Medical Journal Corp. Ltd, 2026)
Introduction: Nasolacrimal duct obstruction (NLDO) is the most common cause of impaired tear drainage and typically presents with excessive tearing and/or recurrent infection. Although medical treatment, such as antibiotics may provide symptomatic relief, definitive management, typically external and endonasal dacryocystorhinostomy (DCR) is usually required. Several variations of DCR have been described, including procedures with silicone intubation. However, the role of silicone intubation in DCR remains controversial, with differing opinions regarding its clinical benefit. Methods: This study was conducted following PRISMA guidelines. A thorough literature search was performed across four electronic databases: PubMed, ScienceDirect, Semantic Scholar, and Google Scholar. The search strategy was designed to identify studies evaluating DCR performed with and without silicone tube insertion in patients with NLDO. The primary outcomes of interest included anatomical and functional patency and the presence of persistent epiphora. Result: Fourteen studies were included in the analysis. Symptom improvement occurred in patients with and without silicone intubation, typically within weeks and maintained through follow-up. Patency was assessed by various methods, and tube removal timing varied. Most studies found no statistically significant differences in functional or anatomical outcomes between the two groups. Conclusion: This review suggests that the role of silicone intubation is similar in both external and endonasal dacryocystorhinostomy. While some studies show a trend toward higher success with intubation, few report statistically significant improvements. Silicone tubes are associated with longer operative times, higher costs, and potential complications, yet high success rates are also achieved without them. Therefore, silicone intubation is recommended only for carefully selected patients, considering the surgical approach, anatomy, and risk of failure.